High Prevalence of Metallo-beta-lactamase Producing Acinetobacter baumannii Isolated From Two Hospitals of Tehran, Iran - Maryam Noori; Abdollah Karimi; Fatemeh Fallah; Ali Hashemi; Shadi Alimehr; Hossein Goudarzi; Shadi Aghamohammad (2014)
Background:: Metallo-beta-lactamase (MBL)-producing Acinetobacter baumannii is a growing therapeutic concern, worldwide. Objectives:: The aim of this study was to determine the frequency of SPM and IMP type genes among A. baumannii isolates from hospitalized patients in Loghman Hakim and Milad hospitals, Tehran-Iran from 2012 to 2013. Patients and Methods:: This study was conducted on 108 A. baumannii isolates collected from two hospitals in Tehran, Iran. Antibiotic susceptibility tests were performed by Kirby-Bauer disc diffusion and Broth microdilution methods according to clinical laboratory standards institute (CLSI) guidelines, and combined disk diffusion test (CDDT) was performed for identification of metallo-beta-lactamases (MBLs). The blaIMP and blaSPM genes were detected by PCR and sequencing methods. Results:: The resistance of A. baumannii isolates against tested antibiotics were as follow: 108 (100%) to cefotaxime, 103 (95.4%) to ceftazidime, 99 (91.7%) to meropenem, 99 (91.7%) to imipenem, 44 (40.7%) to gentamicin, 87 (80.6%) to amikacin, 100 (92.6%) to ciprofloxacin, 105 (95.7%) to cefepime, 105 (97.2%) to piperacillin, 103 (95.4%) to piperacillin/tazobactam, 106 (98.1%) to ampicillin/sulbactam, 106 (98.1%) to co-trimoxazole, 87 (80.6%) to tetracycline and 1 (1.8%) to colistin. Using combined disk diffusion test, it was found that out of 99 imipenem non-susceptible A. baumannii strains, 86 (86.86%) were MBL producers. The prevalence of IMP-1 gene among metallo-beta-lactamase-producing A. baumannii isolates was 3 of 86 (3.48%). Conclusions:: The prevalence of metallo-beta-lactamase-producing A. baumannii strains detected in this study is of great concern and highlights the need of infection control measures including antibacterial management and prompt identification of beta-lactamase-producing isolates.